(3GdfGaY GdcHjQs - (3eMeO YHO GdMi Gddcfhis; (3eMeO GdTjHGfj , eMeO Hf GdMSf GdTjHGfj, GdTjHGfjs
(3ChdgG (B:s
(3NjQ GdCeGdi EedGA MeO GdQH GdeJYGdi CeG HYO ajbhd GdYHO GdQGLi GdQMeI QHg Gdbhi CHhGdMSfGJ eMeO YHO GdMi Gddcfhi GdMfai deG habfi dJMTjI GdLGeY GdUZjQ ef JUGfja eMeO Hf GdMSf GdTjHGfi GdaUd GdChd ai PcQ WHbGJ GdabgGA s
(3BNQgG (B:s
(3hbO JTQaJ ai GdefGe HRjGQI SjOfG CHj HcQ hYeQ hGHf YHGS MjHf EbGeJi HGdhWf MaXg Gddg Yf TQag GdeDef s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs